Chemical composition and biological activities of essential oil and extracts from Ocimum sanctum. Issue 7 (3rd July 2017) - Hussain, Abdullah Ijaz; Chatha, Shahzad Ali Shahid; Kamal, Ghulam Mustafa; Ali, Muhammad Adnan; Hanif, Muhammad Asif; Lazhari, Muhammad Ibrahim
ABSTRACT: The objective of the present research work was to evaluate the antioxidant, antimicrobial and antimalarial activities of essential oil and various extracts from O. sanctum . Gas chromatography-mass spectrometry analysis identified the following major compounds with their quantification as: eugenol (22.0%), β-elemene (19.2%), β-caryophyllene (19.1%), and Germacrene D (5.03%). HPLC analysis of O. sanctum extracts revealed that gallic acid, chlorogenic acid, p -hydroxy benzoic acid, caffeic acid, vanillic acid, p -coumeric acid, sinapic acid, and ferulic acid were the important phenolic acids. The methanol extract exhibited highest level of total phenolic (1.36 g/100 g dry plant material) and total flavonoid (0.67 g/100 g dry plant material) followed by ethanol and n -hexane extracts. The oil and extracts exhibited excellent free radical scavenging potential as measured by 2, 2-diphenyl-1-picrylhydrazyl radical free radical-scavenging ability, and antioxidant activity as measured by inhibition of linoleic acid oxidation. Essential oil, n- hexane, methanol, and ethanol extracts exhibited moderate antimalarial potential in term of anti-haem biocrystallization activity. In the resazurin microtitre plate and disc diffusion assays, the essential oil of O. sanctum showed better antibacterial activity than various extracts. The results of the present investigation demonstrated significant ( p < 0.05) variations in the antioxidant, antimicrobial, and antimalarial activities of essential oil and extracts from O. sanctum .